KAJIAN PERAN SUSU SKIM DAN BAKTERI ASAM LAKTAT PADA MINUMAN SINBIOTIK UMBI BENGKUANG (pachyrrhizus erosus) - Mulyani, Tri; HP, Sudaryati; Susanto, Agus (UPN VETERAN JAWA TIMUR, 2011)
Sinbiotik (eubotic) is a combination of prebiotics and probiotics. The advantage of this combination is to enhance the growth of probiotic bacteria by prebiotic substrates. In general, the raw material of sinbiotik beverage is milk. At this time, as product innovations made brew filtrate sinbiotik of yam tubers (Pachyrrizus erosus). The advantages of this product is the availability of two components as well as the inulin derived from the tubers of yam which acts as a prebiotic and Lactobacillus Casei that act as probiotics. The purpose of this study was to determine the effect of the addition of skim milk and the concentration of starter (Lactobacillus casei) that most optimally in the process of making drinks sinbiotik yam tubers. The results showed that the best treatment there is the additional treatment of skim milk 20% and the concentration of starter (Lactobacillus Casei) 2%. The results showed total lactic acid bacteria 11.2933 log CFU / ml, 0.5119% total acid, pH 3.7, total dissolved solids 36.0680 (oBrix), inulin content of 3.2503% and 0.3667% soluble protein.Keywords: sinbiotik, skim milk, probiotic bacteria, prebiotic substrates